Ground ice and hydrothermal ground motions on aufeis plots of river valleys - V. R. Alekseev (Лëд и снег, 2015)
Localized groundwater outflow and layered freezing of them in forms of large ice clusters on the surface creates specific conditions for energy and mass exchange in the «atmosphere–soil–lithosphere» system. In winter, the soil temperature profile is essentially deformed due to heat emission by the aufeis layer of water at its freezing that forms a specific thermocline layer. Deformation of the temperature profile, gradually decreasing, moves down the cross-section and disappearing at the interface between frozen and thawed rocks. Magnitude and number of the temperature deviations from a «normal» state depends on the heat storage of the aufeis-forming waters and on the number of outflows at a given point. The thermocline formation changes conditions of freezing for underlying ground layers together with mechanism of ice saturation of them, and that results in formation of two-layer ice-ground complexes (IGC) which differ drastically from cryogenic features in adjacent parts of the valley. Analysis of genetic characteristics and relation of components of the surface and subsurface layers allowed identification of seven types of the aufeis IGC: massive-segregation, cement-basal, layered-segregation, basal-segregation, vacuum-filtration, pressureinjection, and fissure-vein. Yearly formation and destruction of aufeises and subsurface ices is accompanied by a sequence of particularly hazardous geodynamical phenomena, among which the most important are winter flooding of territories, layered freezing of water, ground heaving, thermokarst, and thermoerosion. Combination of these processes may cause a rapid (often unexpected) reconfiguration of channels of both surface and subsurface runoff, abrupt uplifts and subsidences of the surface, and decompaction and «shaking-up» of seasonally thawing and seasonally freezing rocks, which may create exceptionally unfavorable conditions for construction and operation of engineering structures. Aufeis plots of river valleys are the most «hot» points of the permafrost zone. A comprehensive study of them requires organization of several reference aufeis test areas located in different natural-climatic and geocryological zones. In addition to the natural-historical and methodological aspects, the future research program should include consideration of problems related to interaction between engineering structures and aufeis events and aufeis ice-ground complexes.